2013
DOI: 10.3109/08941939.2013.856497
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing 4-Port, 3-Port, and Single-Incision Laparoscopic Cholecystectomy

Abstract: SILC is associated with less postoperative pain in later hours, reduces in-hospital analgesic dosages, has longer procedure time, but does not increase intraoperative and postoperative adverse events It seems that SILC has no obvious advantages in terms of later outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
1
32
1
1
Order By: Relevance
“…One trial had a 1·5 : 1 allocation ratio, with more patients in the SILC group. Another trial allocated patients equally to four‐port, three‐port and single‐port laparoscopic cholecystectomy; the four‐ and three‐port groups were analysed as a single group, resulting in a 2 : 1 ratio. A third study had a 2 : 1 allocation ratio with fewer patients in the MLC group.…”
Section: Resultsmentioning
confidence: 99%
“…One trial had a 1·5 : 1 allocation ratio, with more patients in the SILC group. Another trial allocated patients equally to four‐port, three‐port and single‐port laparoscopic cholecystectomy; the four‐ and three‐port groups were analysed as a single group, resulting in a 2 : 1 ratio. A third study had a 2 : 1 allocation ratio with fewer patients in the MLC group.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting a readmission rate of ≥ 5% had an average cohort size of 15,000, whereas studies reporting a readmission rate of < 5% had an average cohort size of 44,000. There were three studies that reported a readmission rate > 7%; these include Vohra et al [43] based in the UK and Ireland (7.1%), Fuks et al [19] based in France (9.5%) and Nielsen et al [31] based in Denmark (11.7%).…”
Section: Readmission Ratementioning
confidence: 99%
“…Data were pooled into one MLC group for the following reasons: a) only 3 other trials used exclusively a 3-port MLC and two trials combined the 3-port and 4-port approaches not making a distinction. Therefore, there was too few data to compare SILC separately to a 3-port and a 4-port MLC; b) the results for the two MLC approaches in this one trial 43 were practically identical. Trials also varied regarding the gallbladder retraction methods in SILC, inclusion/exclusion criteria and analgesic strategies (not shown), and blinding (Table 4).…”
Section: Characteristics and Quality Of The Included Trialsmentioning
confidence: 99%